Mercury, Polychlorinated Biphenyls, Selenium, and Fatty Acids in Tribal Fish Harvests of the Upper Great Lakes. Issue 10 (11th May 2018) - Dellinger, Matthew J.; Olson, Jared T.; Holub, Bruce J.; Ripley, Michael P.
Abstract: The Chippewa Ottawa Resource Authority monitors fish contaminants in Anishinaabe (Great Lake Native American) tribal fisheries. This article updates previously reported trends in two persistent bioaccumulative toxic (PBT) substances that are the primary contributors to consumption advisory limits for these fish: methylmercury (MeHg) and polychlorinated biphenyls (PCBs). Also, we report, for the first time, an analysis of nutritional benefit bioindicators and metrics in these same Upper Great Lakes fish harvests: selenium (Se) and omega‐3 fatty acids (PUFA‐3s). A novel risk/benefit quantification originally presented by Ginsberg et al. is reported here to characterize the tradeoffs between fatty acid benefits and toxic MeHg health outcomes. We also report a Se benefit metric to characterize the possible protective value against MeHg neurotoxicity based on Ralston et al. Congruent with Anishinaabe cultural motivations to consume fish from their ancestral fisheries, nutritional content was high in locally caught fish and, in some respects, superior to farmed/store‐bought fish. These Great Lakes fish still contained levels of PBTs that require careful education and guidance for consumers. However, the contaminant trends suggest that these fish need not be abandoned as important (both culturally and nutritionally) food sources for the Anishinaabe who harvested them.